PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR MATEMATIKA OPERASI HITUNG CAMPURAN SD COKROAMINOTO PANGIA - Sri Intanita Bidjuni; Lian G. Otaya; Ingka Rizkyani Akolo (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine the effect of the use of audio-visual media on the learning outcomes of mixed arithmetic operations in elementary school COKROAMINOTO Pangia, South Bolaang Mongondow Regency. This study was measured using experimental research and conducted an experimental class to determine the use of audio-visual media. With a sample of 9 respondents. This study used a simple regression tool. Based on the formulation of the problem that has been determined, the method used in this study is quantitative descriptive analysis or a quantitative approach. The reason is that in implementing actions to research objects, detailed explanations are prioritized. Based on the results of research conducted on students at SD COKROAMINOTO Pagia, the results of the study were obtained, namely the rxy value of 5.363. When consulted with the r table product moment with the number of samples (N) = 9, at a significance level of 0.05, r table = 2.365 was obtained and at a level of 1%, r table = 2.365 was obtained. According to Sugiono (2012). If r count is smaller than r table (rh<rt), then H0 is accepted, and Ha is rejected. But conversely, if r count is greater than r table (rh>rt), then Ha is accepted. In accordance with the calculation results, r count (5.363) is greater than r table (2.365). Then the proposed hypothesis (Ha) is declared accepted.